'A Tale of Two Slippers' : Uncanny parody, power and the performance of writing - Hunn, Deborah (2018)
In this combined critical and creative work, my experimental short story ‘A Tale of Two Slippers’ (in which a character escapes a text to kill her author) is framed through an introduction in which cultural studies theory and reflections on practice-led research provide insights into how parody and the performance of writing can work uncannily and generatively to resist the power relations embedded in conventions of genre and the author/text binary. The key focus is on parody, and its uncannily doubled discourse (Barfield and Tew, 2002), which combines with the added critical edge of metafiction and ontological/textual slippage, to explore the creative potential of Australian cultural engagement with hegemonic conventions of judgement and genre, and to consider the subversive edge that writing from the margins might bring to this endeavour.